VALTOCO® (Diazepam Nasal Spray) for the Acute Treatment of Intermittent Stereotypic Episodes of Frequent Seizure Activity - Elyse M. Cornett; Sam N. Amarasinghe; Alexis Angelette; Tunde Abubakar; Adam M. Kaye; Alan David Kaye; Elisa E. Neuchat; Ivan Urits; Omar Viswanath (MDPI AG, 2021)
Valtoco® is a new FDA-approved nasal spray version of diazepam indicated for the treatment of acute, intermittent, and stereotypic episodes of frequent seizure activity in epilepsy patients six years of age and older. Although IV and rectal diazepam are already used to treat seizure clusters, Valtoco® has less variability in plasma concentration compared to rectal diazepam. Furthermore, the intranasal administration of Valtoco® is more convenient and less invasive than rectal or IV diazepam, making it ideal for self-administration outside of a hospital setting. Multiple clinical trials have taken place comparing Valtoco® to the oral, rectal, and IV forms of diazepam. Aside from mild nasal irritation and lacrimation, Valtoco® was found to have no increased safety risk in comparison to traditional forms of diazepam. This review of Valtoco® will include a history of diazepam prescribing and withdrawal treatment, Valtoco® drug information, its mechanism of action, pharmacokinetics and pharmacodynamics, and a comprehensive review of clinical studies.